2022
DOI: 10.1038/s41598-022-24095-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forward head posture on muscle activation pattern of the trapezius pars descendens muscle in young adults

Abstract: Forward head posture (FHP) is a serious problem causing head and neck disability, but the characteristics of muscle activity during long-term postural maintenance are unclear. This study aimed to investigate a comparison of electromyography (EMG) activation properties and subjective fatigue between young adults with and without habitual FHP. In this study, we examined the changes in the spatial and temporal distribution patterns of muscle activity using high-density surface EMG (HD-SEMG) in addition to mean fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…[26][27][28]31 On the other hand, there was no difference in muscle activation during shoulder flexion and abduction according to low load because it already has increased activity of the UT, decreased activity of SA, and lower endurance in FHP. 30,31 Because of mild FHP, it is suggested that there might be no significant correlation between FHP and muscular activation in the present study. In addition, when the posture is stable, the muscle activity increased in the SA and pectoralis major as the load increased, but the UT showed constant muscle activity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…[26][27][28]31 On the other hand, there was no difference in muscle activation during shoulder flexion and abduction according to low load because it already has increased activity of the UT, decreased activity of SA, and lower endurance in FHP. 30,31 Because of mild FHP, it is suggested that there might be no significant correlation between FHP and muscular activation in the present study. In addition, when the posture is stable, the muscle activity increased in the SA and pectoralis major as the load increased, but the UT showed constant muscle activity.…”
Section: Discussionmentioning
confidence: 57%
“…In previous studies reported that FHP changed according to the muscle length and muscle tension, such as sternocleidomastoid, neck extensor, trapezius, SA, and pectoralis. 7,[29][30][31] In FHP, increased muscle activation of the UT and decreased muscle activation of the SA were noted during shoulder flexion and abduction. [26][27][28]31 On the other hand, there was no difference in muscle activation during shoulder flexion and abduction according to low load because it already has increased activity of the UT, decreased activity of SA, and lower endurance in FHP.…”
Section: Discussionmentioning
confidence: 99%
“…15 People with FHP showed abnormal electromyographic (EMG) activity in the neck muscles, and it was reported that shoulder muscles, such as the serratus anterior and trapezius muscle, were also negatively affected. 12,16 Objective and quantitative clinical investigations are important in determining the precise diagnosis for patients with musculoskeletal dysfunctions, such as FHP and neck problems. 2,7 Many previous studies related to FHP and the kinesiologic function of the shoulder complex reported the effects of FHP on EMG activity of the shoulder muscles, such as the upper trapezius, serratus anterior, or lower trapezius.…”
mentioning
confidence: 99%
“…2,7 Many previous studies related to FHP and the kinesiologic function of the shoulder complex reported the effects of FHP on EMG activity of the shoulder muscles, such as the upper trapezius, serratus anterior, or lower trapezius. 12,16 Although high-quality kinetic and kinematic evaluations, such as a 3D motion analysis and EMG devices, are used to investigate the relationship between FHP and shoulder dysfunction, most of the studies have mainly focused on shoulder muscle activity or neck pain. 2,3,16 In addition, studies verifying the effect of artificial FHP on the kinetics and kinematics of the shoulder joint using internal and external movement tasks are insufficient.…”
mentioning
confidence: 99%
See 1 more Smart Citation